DESENVOLVIMENTO DE UMA TECNOLOGIA EDUCATIVA PARA MÃES E CUIDADORES DE RECÉM-NASCIDOS PREMATUROS - Cauzzo, Larissa Dalla Corte (2023)
Prematurity is a public health problem and a determining factor in infant mortality. The third sustainable development objective proposed by the United Nations, in health and well being, in item 3.2, by 2030, is to end preventable deaths of newborns and children under five years of age. Objectives: To understand and characterize the perceptions and needs of mothers regarding the care of premature newborns at home. Furthermore, we sought to develop and validate an educational technology to assist mothers and caregivers in caring for premature newborns at home.Methodology: To prepare the technological product, two stages were carried out, one investigative and one construction. The first was developed in January 2023, in a municipality in the interior of Rio Grande do Sul. Eleven mothers of premature newborns participated in the sample, who were elected through snowball sampling. This study followed the recommendations of the Consolidated criteria for reporting qualitative research, which is suggested for research reports that collect data through interviews or focus groups. The second stage of the study consisted of developing the educational technology of the web site, which was developed in three phases: pre-production, production and post-production of the content. The first pre-analysis stage is called the organization phase, the second production phase of material exploration is characterized by the analysis itself and the third class is the content analysis process which was the treatment of the results Results: Regarding mothers' perceptions and needs, three categories were extracted: the first was preparation for hospital discharge of premature newborns, the second category, covid-19 a link with prematurity and finally, search for information about newborns. born born prematurely. Some mothers take their newborn home feeling very unprepared for this reality, transmitting feelings of fear, insecurity and fragility when touching the newborn. The website “Prematurar: Prematuro Bem Care” was built containing the categories of preparation of the website “Prematurar: Prematuro Bem Care”, brand building, technology development, social impact, website validation process, where there is content in text format and videos, which will continue to be developed for at least five years. The experts who validated it considered it an extremely important, safe and quality product in the area of care for premature newborns. Final considerations: This study allowed us to understand the experiences and perceptions of mothers of premature newborns regarding home care and to verify the need for easily accessible instruments for mothers and other caregivers to consult. Technological product and its applicability: The web page “Prematurar: Prematuro Bem Cared”, which is aimed at the demands of mothers of premature newborns and the general public who are interested in the topic. Its applicability lies in providing information on various subjects, such as hygiene, sleep, nutrition and other special care that premature newborns need at the beginning of their journey, in a friendly and appropriate way and with technical property, based on scientific evidence.